ANALISIS PENERAPAN SISTEM PENGENDALIAN MUTU DALAM MENINGKATKAN EFEKTIVITAS PERENCANAAN AUDIT KANTOR AKUNTAN PUBLIK ABC - Ratih Puspitasari; Rudi Ginting; Andi Manggala Putra (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2020)
This research is using qualitative reasearch method with etnomethodology approach and interpretive paradigm that aims to know the suitability and compliance of quality control policies established by KAP ABC with the SPAP. Quality control policies set forth in the Quality Control Standard (SPM) number 1 year 2013 which has been set by the Indonesia Institute of Public Accountant (IAPI), SPM is consisted of six elements, namely the leadership of KAP’s leadership, applicabel ethical and professional provisions, acceptance and sustainability of relationships with clients and certain engagement, human resources, impelemntation of alliances, and monitoring. Also to find out the implementation quality control system to improving audit planning effectiveness of Public Accounting Firm ABC. The data were obtained from observation, interviews, and documentation. The results showed that the SPM set in KAP ABC was already accordance with SPM number 1 year 2013 by IAPI, But for the documentation of consultant with external parties need to be improved. The results of this research showed that quality control system in improving audit planning effectiveness which is be the guideline for KAP to carrying out assingments by prioritizing quality and assisting auditors in determining risks, by conducting first survey of the prospective client for consideration in accepting clients, make a time schedule that suits the actual situation, including preparing competent and professional auditors, as well as preparing adequate testing and conduct discussions and consultations of any conditions that require more attention.